Exploring Halal Lifestyle in the Consumption Behavior of Muslim Generation Z in Indonesia - Sofi Qurniawati; Prayogi Restia Saputra (Universitas Negeri Surabaya, 2026)
This study aims to explore the implementation of halal lifestyle in the consumption behavior of Muslim Generation Z in Indonesia. The study employs a qualitative approach using a library research method by analyzing various relevant scientific sources, including journals, books, research reports, and official publications related to halal lifestyle, halal awareness, religiosity, digital media, and Muslim consumer behavior. Data were collected through documentation techniques and analyzed using content analysis and thematic analysis. The findings indicate that halal lifestyle has developed beyond a religious obligation and has become part of the social identity and modern lifestyle of Muslim Generation Z. The study reveals that halal awareness, religiosity, and digital media play significant roles in shaping halal consumption behavior. Digital platforms facilitate access to halal-related information and contribute to the dissemination of halal lifestyle trends among young Muslims. However, challenges such as misinformation, halal washing practices, and increasing consumerism in the digital era may hinder the optimal implementation of halal lifestyle. This study contributes to the development of halal consumer behavior literature by providing a comprehensive understanding of the factors shaping halal lifestyle among Muslim Generation Z in Indonesia.